Monetary Policy and Exchange Rates Pre- and Post-Global Financial Crisis: The Case of Turkey - Isiksal, Aliya Z.; Samour, Ahmed; Resatoglu, Nil Gunsel (Journal of History Culture and Art Research, 2018)
The aim of this study is to investigate the association between monetary policy and exchange rates in Turkey for two periods: Pre (December 2001-December 2007) and Post (January 2010-January 2016) global financial crisis (GFC). The ARDL, FMOLS, CCR and DOLS models are used to achieve the objective of this study. The results show that there is a significant impact of monetary policy, namely money supply and short-term interest rates, on exchange rates in Turkey before and after the GFC. The results suggest that the Central Bank of Turkey affected exchange rates after the GFC more than before the GFC.